Congenital hypothyroidism screening by umbilical cord blood thyroid stimulating hormone: a cross sectional study - R. N., Karthik; S., Udayakumar; K., Pratibha; K., Pushpalatha (International Journal of Contemporary Pediatrics, 2023)
Background: Congenital hypothyroidism is one of the most important and common preventable cause of intellectual disability. The objective of the study is to determine the proportion of congenital hypothyroidism among newborn babies delivered at ESIC-MC and PGIMSR Hospital, Bangalore. Methods: Present study was a cross sectional study conducted in the Department of Paediatrics, ESICMC and PGIMSR over a period of 18 months from march 2021 to august 2022. All babies wherein the cord blood TSH was found to be over 20 mIU/l will be intimated within 24 hrs of the test. The babies were advised to give fresh samples TSH on day 3. Results: In the present study, of the 1900 deliveries, cord blood was available for 1669 newborns. Of the 1669 newborns, 3.1% (N=51) newborns had cord blood TSH more than 20 mIU/l and remaining 96.9%(n=1618) had cord blood TSH levels of less than 20 mIU/l. Out of 51 newborn who were screened positive for congenital hypothyroidism were subjected to futher testing by serum TSH on day 3. Serum TSH on day 3 levels was high (>20 mIU/l) 11.7% (N=6) neonates and serum TSH (<20 mIU/l) 88.2% (N=46) neonates. In this study, the proportion of congenital hypothyroidism was 0.4% (N=6) which was 1 in 278 babies delivered. Conclusions: The present study adds emphasis on the need for continuing screening for congenital hypothyroidisn, one of the preventable cause for intellectual disability. In developing countries, incidence is very high, the need for screening programs is the need of the hour.